Path of the prophets : the ethics-driven life - Schwartz, Barry L. (Philadelphia : University of Nebraska Press, 2018)
"Devoted to the legacy of the biblical prophets, identifies the prophetic moment in the lives of 18 biblical characters, offers up an intimate view of their inner thoughts, illuminates their ethical legacies, and challenges each of us to walk the path of the prophets today"--
Preface: Why the Prophets? -- Introduction: The Ethics-Driven Life -- Part 1. To Do Justly -- 1. Abraham's Argument: The Path of Protest -- 2. Shiphrah's Defiance: The Path of Civil Disobedience -- 3. Moses' Encounter: The Path of Freedom -- 4. Tirzah's Challenge: The Path of Equality -- 5. Samuel's Warning: The Path of Rebuke -- 6. Nathan's Parable: The Path of Righteousness -- Part 2. To Love Mercy -- 7. Judah's Step Forward: The Path of Repentance -- 8. Joseph's Cry: The Path of Forgiveness -- 9. Ruth's Vow: The Path of Kindness -- 10. Elisha's Invitation: The Path of Healing -- 11. Jeremiah's Scroll: The Path of Hope -- 12. Jonah's Lesson: The Path of Compassion -- Part 3. To Walk Humbly -- 13. Miriam's Celebration: The Path of Joy -- 14. Caleb's Spirit: The Path of Faith -- 15. Hannah's Prayer: The Path of Prayer -- 16. Elijah's Voice: The Path of Humility -- 17. Isaiah's Vision: The Path of Peace -- 18. Ezra's Torah: The Path of Wisdom -- A Prophetic Glossary -- Study Guide: Living the Bible.
Print version record and CIP data provided by publisher.
Includes bibliographical references.
JSTOR
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc., Jewish; Bible; Prophets -- Biography; Justice -- Biblical teaching; Jewish ethics -- Biblical teaching; PROPHETS; Prophètes -- Biographies; Morale juive -- Enseignement biblique; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Judaism -- Sacred Writings; Justice -- Biblical teaching; Prophets; Biographies; Criticism, interpretation, etc